Post-tensioned masonry. A constructive alternative to Ecuador and seismic regions - Zalamea León, Esteban (Universidad de Cuenca, 2013)
This work addresses a central problem of construction in Cuenca, Andean city of the South of the Ecuador, where every day we see that mostly, failure to comply with the provisions of the regulations that govern other countries with similar seismic conditions, so it is visible that the buildings are at serious risk. From this evidence, our research seeks to construct masonry walls post-tensioned with materials, tools and techniques available in the medium, considering that the proposed construction technology and adapted for masonry is already a response in other societies, with the same potential risks.Keywords: Architecture post-tensioned, masonry, building, Ecuador.